A comparison of sarcopenia prevalence between former Tokyo 1964 Olympic athletes and general community‐dwelling older adults - Tomoki Tanaka; Takashi Kawahara; Hiroshi Aono; Sachiko Yamada; Soya Ishizuka; Kyo Takahashi; Katsuya Iijima (Journal of Cachexia, Sarcopenia and Muscle, 2021)
Abstract Background This study aimed to determine how increased muscle mass and athletic performance in adolescence contribute to the prevention of sarcopenia in old age, accounting for the type of sport and the continuation of exercise habits. We compared the prevalence of sarcopenia, its components (low appendicular skeletal muscle mass, low muscle strength, and low physical function), and musculoskeletal pain using data from two cohorts: former athletes who competed in the 1964 Tokyo Olympics and general community‐dwelling older adults living in Kashiwa City, Chiba Prefecture. Methods We analysed the data from 101 former Olympic athletes (mean age ± SD: 75.0 ± 4.4 years; 26% female) and 1529 general community‐dwelling older adults (74.1 ± 5.5 years; 49% women). We assessed sarcopenia (defined by the Asian Working Group for Sarcopenia revised in 2019) and musculoskeletal pain and considered potential confounding factors such as demographic characteristics, for example, sex and exercise habits. Results The prevalence of sarcopenia was significantly lower in former Olympic athletes than general older adults (odds ratios [OR], 0.49; 95% confidence interval [CI], 0.20–0.94), especially with regard to superior appendicular skeletal muscle mass and muscle strength. This effect was more pronounced in individuals who continued their exercise and in athletes whose sporting discipline was classified as having a high exercise intensity. Conversely, low physical function (OR, 2.60; 95% CI, 1.16–6.07) and musculoskeletal pain (OR, 2.22; 95% CI, 1.24–3.97) were more prevalent in former Olympic athletes and in athletes who competed in sports with physical contact. Conclusions We observed a lower prevalence of sarcopenia and superior appendicular skeletal muscle mass and strength in the former Olympic athletes, especially among those that continued their exercise habits and those in sports with high exercise intensity. Conversely, low physical function and higher musculoskeletal pain scores were more prevalent in former Olympic athletes, especially among athletes who competed in sports with physical contact. Our results warrant further promotion of exercise in adolescence and beyond as well as providing safety education, which is required to prevent the development of sarcopenia and musculoskeletal pain in old age.